First reliable fossil record of the subfamily Rhysipolinae (Hymenoptera: Braconidae): a new subgenus and species of the genus Rhysipolis Foerster, 1863 from Baltic amber - Belokobylskij, Sergey A.; Manukyan, Andranik R. (Zootaxa, 2024)
A new fossil subgenus and species of the genus Rhysipolis Foerster, 1863 from the subfamily Rhysipolinae, Rhysipolis (Granulopolis) simutniki Belokobylskij, subgen. et sp. nov., are described and illustrated from late Eocene Baltic amber. The genus Trichelyon Ortega-Blanco & Engel, 2012 is synonymised with Clinocentrus Haliday, 1833 (syn. nov.) and a new combination, Clinocentrus tadkeshwarense (Ortega-Blanco & Engel, 2012), comb. nov., is suggested. The status of the previously described species in the subfamily Rhysipolinae are discussed.